Exemplary Model of Teachers in Fostering Student Morals in Aceh Utara District, Indonesia - Hajar, Ibnoel; Syabuddin, Syabuddin; Mahmud, Salami; Furqan, Muhammad (International Journal of Social Learning (IJSL), 2024)
Digital globalisation has changed the paradigm, lifestyle, and value system that has resulted in the decline of the nation's morals and character, including in education. This research aims to 1) analyze the model of teacher exemplary in fostering student morals; 2) explain the strategy of moral development based on teacher exemplary; and 3) evaluate the transformation of student morals through teacher exemplary. The research uses a descriptive qualitative approach with primary and secondary data collected through observation, interviews, and documentation. The results show that exemplary personality, behavior, and speech teachers significantly foster student morals, although it is not fully realized in the classroom. Strategies based on responsibility, courtesy, and discipline require consistency and time for significant moral transformation. Programmed and explicit coaching, accompanied by teacher commitment to providing real examples, encourages students to adopt positive behaviors in their daily lives.